PRODUKTIVITAS DAN BIAYA ALAT HASIL REKAYASA DALAM PENGELUARAN KAYU JATI DI DAERAH CURAM - Wesman Endom (BRIN Publishing, 2013)
This study deals with the trial on teak wood-log extraction on a steep terrain using skyline system. This system used a small capacity yarder machine (5.5 PK) of generation II's Expo prototype. The wood log was pulled from a tree-felling plot all theway about 50-m distance to the bill slope. As such, the yarder afforded the productivity in average 0.6263 m²/hour, implying that it was still below the targeted range (2.5-5m/bour). The investment cost reached Rp 72,000,000 or correspond to Rp 102,986/bour or Rp 156,351/ ni'. Financial analysis using the actual performance of such tool at the rents price similar to the log-extracting cost brought out negative NPV and IRR values. Such values could have been positive had the rents price been greater, equal to Rp 185,000/m².